Tecnologia dell'architettura: creatività e innovazione nella ricerca Materiali del I Seminario OSDOTTA (Viareggio, 14-16 settembre 2005) - Esposito, Maria Antonietta (Scuole di dottorato, 2006)
The book inaugurates a series of publications created to enhance the activity conducted in the Research Doctorates of Technology of Architecture and it does so by presenting the results of the first seminar of the Italian DdR. The didactic and scientific value of this innovative experience is testified by the interventions and by the working themes addressed which outline the research scenario and the proposals for the future. For this reason, the volume and the series have a didactic function at several levels (orienting those who approach the subject on the contents that the sector deals with in Italy) and as a tool for professional training aimed at achieving the highest quality levels.